Helminths from Lizards (Reptilia: Squamata) at the Cerrado of Goias State, Brazil - Avila, Robson W. [UNESP]; Cardoso, Manoela W.; Oda, Fabricio H.; Da Silva, Reinaldo J. [UNESP] (Helminthological Soc Washington, 2011)
Forty-three specimens representing 11 species of lizards (Ameiva ameiva, Anolis chtysolepis brasiliensis, Cnemidophorus cf. parecis, Hemidactylus mabouia, Mabuya dorsivittata, Mabuya nigropunctata, Ophiodes striatus, Philautus acutirostris, Tropidurus itambere, Tropidurus oreadicus, and Tupinambis merianae) collected in 6 localities of the Cerrado biome in the Brazilian state of Goias were examined for helminths. Thirteen species of nematodes (Cruzia travassosi, Gynaecometra bahiensis, Oswaldofilaria sp., Parapharyngodon sp., Parapharyngodon largitor, Paraphatyngodon sceleratus, Pharyngodon travassosi, Physaloptera sp., Physaloptera lutzi, Physaloptera retusa, Physalopteroides venancioi, Subulura lacertilia) and an unidentified species of cestode (Oochoristica sp.) were recovered from lizard hosts. Thirteen new host records and 7 locality records are reported.
Keywords: Nematoda; Cestoda; Squamata; Sauna; Brazil; Neotropical; South America